Bureaucratic Behavior in Increasing Community Participation: Study of the Implementation of Village Development - Nurhayati Doran; Muhamamd Guzali Tafalas; Rulinawaty Rulinawaty (Borong Newinera Publisher, 2024)
This study investigated the impact of bureaucratic conduct on promoting community involvement in village development and evaluated and analyzed the behavior of bureaucrats. This research employs a qualitative descriptive design. This study gathers data via four distinct stages: pre-field, field work, data processing, and report writing. Community participation at every level or process of development is crucial for achieving success, as shown by the study findings. Community participation is a crucial aspect of development and serves as an indicator of its efficiency, but it often remains insufficient. The lack of community participation in the development process may be attributed to the ineffectiveness of bureaucratic leadership, communication, and education, resulting in poor operation of the process. The coordination between District Heads, Service Branches, and District Level Agencies has not been in accordance with the work program. The community in Wasior District lacks education, rendering them devoid of authority and unable to make informed decisions on development programs that align with their specific requirements. There has been a deficiency in the implementation of efficient village administration and direction for community institutions. Government-led development initiatives have overwhelmingly overshadowed ongoing development efforts in the last 5 years, neglecting the aspirations and requirements of local communities. Community property ownership policies impede both economic progress and community involvement.